2003
DOI: 10.1037/0894-4105.17.3.439
|View full text |Cite
|
Sign up to set email alerts
|

Music training improves verbal but not visual memory: Cross-sectional and longitudinal explorations in children.

Abstract: The hypothesis that music training can improve verbal memory was tested in children. The results showed that children with music training demonstrated better verbal but not visual memory than did their counterparts without such training. When these children were followed up after a year, those who had begun or continued music training demonstrated significant verbal memory improvement. Students who discontinued the training did not show any improvement. Contrary to the differences in verbal memory between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
359
11
36

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(449 citation statements)
references
References 47 publications
33
359
11
36
Order By: Relevance
“…Além disso, há estudos que demonstram a interação entre conhecimentos musicais e a memória operacional em tarefas relacionadas à span de dígitos e memória visuo-espacial (Blundell, Jones, & Kviklyte, 2007;Fujioka, Ross, Kakigi, Pantev, & Trainor, 2006;Ho, Cheung, & Chan, 2003;Parbery-Clark, Skoe, Lam, & Kraus, 2009;Rauscher & Zupan, 2000).…”
unclassified
“…Além disso, há estudos que demonstram a interação entre conhecimentos musicais e a memória operacional em tarefas relacionadas à span de dígitos e memória visuo-espacial (Blundell, Jones, & Kviklyte, 2007;Fujioka, Ross, Kakigi, Pantev, & Trainor, 2006;Ho, Cheung, & Chan, 2003;Parbery-Clark, Skoe, Lam, & Kraus, 2009;Rauscher & Zupan, 2000).…”
unclassified
“…The result showing that the performance of blind and visually impaired young persons in pitch memorization experiment with 4-and 6-tone sequences was almost constant, was reported earlier (Bogusz et al, 2012b). The reports suggesting that musical training is associated with improvements in working memory (Chan et al, 1998;Franklin et al, 2008;Ho et al, 2003;Tierney et al, 2008) have not been confirmed.…”
Section: Pitch Memorization Experimentsmentioning
confidence: 35%
“…There are a number of papers about pitch memory in adult musicians and nonmusician with normal vision (Rakowski, Rogowski, 2007;Rakowski, 2009;Gaab et al,, 2003;Moore et al, 2007). Some studies suggest that training on a musical instrument is associated with improvements in working memory (Chan et al, 1998;Franklin et al, 2008;Ho et al, 2003;Tierney et al, 2008). The working memory ability is one of cognitive factors that is a linker between musical training and production of language sounds through changes in working memory capacity (Posedel et al, 2012; Schellenberg, Peretz, 2008; Acheson, MacDonald, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…D'abord, la perception auditive permet de recevoir et d'analyser les stimuli sonores essentiels à la compréhension d'un message oral ou d'une mélodie (Gómez-Gama, Ávila-Corona, Gómez-Gama, Puente et Ojeda-Morales, 2004). Ensuite, la mémoire verbale favorise la distinction des motifs (regroupements logiques) dans les stimuli sonores (Chan, Ho et Cheung, 1998 ;Ho, Cheung et Chan, 2003). Enfin, les habiletés métacognitives amènent les élèves à gérer activement et consciemment le processus de création de sens (Register, 2001 ;Selway, 2003).…”
Section: Revue Des Sciences De L'éducation De Mcgill • Vol 51 N Ounclassified